Larval habitats of mosquito fauna in Osogbo metropolis, Southwestern Nigeria - Adeleke, Monsuru Adebayo (Asian Pacific Tropical Medicine Press, 2013)
OBJECTIVE: To determine the larval habitats of mosquito fauna and possible impact of land use/ land cover changes on the epidemiology of mosquito-borne diseases in Osogbo metropolis, Southwestern, Nigeria. METHODS: All accessible larval habitats were surveyed between May and September, 2011 in Osogbo metropolis while Land Use/ Land cover of the city was analyzed using 2 Lansat Multispectral Scanner satellite imagery of SPOT 1986 and LANDSAT TM 2009. RESULTS: A total of six species namely, Aedes aegypti, Aedes albopictus, Aedes vittatus, Anopheles gambiae complex, Culex quinquefasciatus and Eretmapodite chrysogaster were encountered during the study. The occurrence and contribution of disused tyres was significantly higher (P<0.05) than the other habitats encountered, while there were no significant differences in the contribution of gutters/run-offs, septic tanks/ drums, ground pools/open drains and discarded containers to the breeding of mosquitoes (P>0.05). The accessible land use/ land covered of the study area between 1986 and 2009 showed that the wet land coverage and settlement area increased from 0.19 to 9.09 hectare and 1.00 to 2.01 hectare respectively while the forest area decreased from 60.18 to 50.14 hectare. CONCLUSION: The contribution of the habitats coupled with the increasing rate of flooded environment which could provide ample breeding sites for mosquitoes call for sustained environmental sanitation and management in Osogbo metropolis.